Analysis of Partnership System in Broiler Chicken Farming from an Islamic Economic Perspective: A Case Study in Padang Karambia, West Sumatera - Fitria Rahma Dian, Aulia; Firdaus, Nil; Rama Bagus Sanjaya, Try; Pratama, Vio (MD Research Center, 2025)
The poultry farming sector, particularly broiler farming in Padang Karambia, Indonesia, has seen rapid growth due to partnership systems between local farmers and large companies like PT Ciomas Adisatwa. This study aims to examine the management of partnership systems in broiler farming and the application of Islamic economic principles, such as justice (adl), cooperation (ta'awun), and fair profit-sharing. The methodology employed is in-depth interviews with three key informants: the broiler farm manager, the Head of the Partner Unit at PT Ciomas, and a Field Extension Officer (PPL). The findings indicate that although the partnership system benefits both parties, there is an imbalance in risk and profit sharing. Farmers, who rely heavily on the facilities provided by the company, feel restricted in setting the selling price of the chickens. In the context of Islamic economics, mudarabah or musyarakah systems can better reflect the principle of justice with a more balanced and transparent profit-sharing. Moreover, the principle of cooperation (ta'awun) needs to be reinforced to foster a more harmonious relationship between the company and farmers. This study recommends the application of a partnership system based on sharia principles to create a more sustainable, just, and mutually beneficial relationship, while strengthening Islamic economic values in broiler farming.